2015
DOI: 10.4236/psych.2015.61001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Integrated Arts Therapy: An Intervention Program for Young Female Offenders in Correctional Institution

Abstract: The aim of the study was to evaluate the impact of program of integrated arts therapy on young female delinquents' who experienced emotional and behavioral problems in a correctional institution. The outlined intervention was introduced as part of a curriculum involving art therapy, drama therapy, music therapy, and dance/movement therapy sessions that were facilitated twice a week during a 5-week period. A quasi-experimental design was used where an intervention group (N = 12) and a control group (N = 17) mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…These results are in the line of several evidence-based prior studies showing that arts-based programs were effective to reduce risk group youngsters delinquent behavior (Clawson & Coolbaugh 2001), externalized (and internalized) behaviors (Rapp-Paglicci et al, 2012), and emotional and behavioral problems (measured by the SDQ) (Cobbett, 2016). Also, multi-modal arts therapy was effective to reduce young offenders' emotional, conduct and aggressive problems with improvement of their prosocial behavior (Kõiv & Kaudne, 2015). In addition, risk group students' emotional problems, hyperactivity, problems with peers, and total difficulties have improved in relation to the implementation of art therapy interventions.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…These results are in the line of several evidence-based prior studies showing that arts-based programs were effective to reduce risk group youngsters delinquent behavior (Clawson & Coolbaugh 2001), externalized (and internalized) behaviors (Rapp-Paglicci et al, 2012), and emotional and behavioral problems (measured by the SDQ) (Cobbett, 2016). Also, multi-modal arts therapy was effective to reduce young offenders' emotional, conduct and aggressive problems with improvement of their prosocial behavior (Kõiv & Kaudne, 2015). In addition, risk group students' emotional problems, hyperactivity, problems with peers, and total difficulties have improved in relation to the implementation of art therapy interventions.…”
Section: Resultssupporting
confidence: 75%
“…20 problems of juvenile delinquents in correctional settings and results revealed significant improvements among intervention group youngsters in the area of prosocial behaviour and reduction of conduct and emotional problems, and aggressive behavior (Kõiv & Kaudne, 2015). The practice-based (Smeijsters et al, 2011) research in comprehensive implication of multi-modal arts therapy programs in correctional institutions have found that these interventions can primary serve to reduce impulsiveness, regulate anger, and increase empathy and compliance of young offenders.…”
Section: Responsibility Of the Organizing Committee Of The Conferencementioning
confidence: 99%
See 1 more Smart Citation
“…Various forms of art therapy have been used in adult forensic psychiatry settings (Smeijsters & Cleven, 2006) and general prisons (Meekums & Daniel, 2011). These include art and drama (Chapman, 2014), music (Hickey, 2018; Pool & Odell‐Miller, 2011), dance (Kiepe, Stöckigt, & Keil, 2012), and integrated (all art forms) art therapies (Kõiv & Kaudne, 2015). When used with general prison samples, art therapy has been demonstrated to reduce violence within the prisons, prison incidents, and rule violations (Brewster, 1983).…”
Section: Delinquency and Art Therapymentioning
confidence: 99%
“…Zanimljivo istraživanje o učinku integrativne art-terapije provedeno je i u Litvi, u jednoj korekcijskoj ustanovi za djevojke, počiniteljicama kaznenih djela u dobi od 14 do 16 godina, koje je pokazalo statistički značajan rezultat kad je riječ o smanjenju frekvencije agresivnog ponašanja, odnosno porastu frekvencije javljanja prosocijalnih ponašanja kod delinkventnih djevojaka koje su sudjelovale u Programu, u odnosu na kontrolnu skupinu (Koiv i Kaudne, 2015). U navedenim primjerima zamjećuje se značajan pozitivan učinak kreativnih tehnika u radu s djecom i mladima rizičnog ponašanja, međutim, mislim da je razvoj kreativnih sposobnosti na ovim prostorima premalo zastupljen u svim životnim područjima i na neki način kreativnost se još uvijek promatra kao privilegij talentiranih umjetnika ili inovatora te velik broj ljudi, osobito djece, uopće nije svjestan vlastitih kreativnih potencijala.…”
unclassified